STORY MAPPING TO TEACH READING NARRATIVE TEXT AND IT’S PROBLEM - Solihati, Nisa; Evenddy, Sutrisno Sadji; Fargianti, Yusti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The purpose of this research is to reveal the process of teaching reading comprehension of narrative texts, and to find out the teacher's problems in applying story mapping techniques in teaching reading comprehension of narrative texts. This study uses qualitative research with a case study method. Data was collected from observation, interviews, and documentation. The participant in this study was an English teacher for class X IPA who taught narrative texts by applying the story mapping technique. The process of teaching and learning reading comprehension is going well, although not optimal. Meanwhile, there are five problems faced by the teacher in teaching reading comprehension, namely the teacher has difficulty if students cannot achieve basic mastery in reading, the teacher has difficulty if students read very slowly the reading text being taught, the teacher has difficulty if students cannot understand and find. conclusions, implications, and main ideas of the reading text, the teacher has difficulties in choosing teaching materials in teaching reading comprehension of narrative texts, and the teacher has problems in designing or modifying questions and exercises to attract students' interest in learning reading comprehension of narrative texts.